Document Management System in Ibnu Sina Middle School Administration - Nofri Yudi Arifin (Engineering and Technology International Journal, 2022)
This study aims to design a management system that can assist staff of SMP Ibnu Sina Batam in storing and collecting incoming and outgoing mail data online. Because there is no document management system related to correspondence storage, it is necessary to design a system. The object of this research is the admin and administrative staff of SMP Ibnu Sina, the modeling method used in the system is Unified Modeling Language (UML) while the system research development method uses Object Oriented Analysis Design (OOAD). The purpose of this research is to provide a solution in helping the Administration of SMP Ibnu Sina Batam in saving files online and numbering letters automatically and helping admins in doing their jobs so that they can complete their work properly and can store data safely. The data collection method used is by conducting interviews and collecting various sources, namely library research, observation. The conclusion in this study is that it is hoped that this system can be implemented by admins and other employees to facilitate performance.